Ricardo Palma, classicism and modernity: Aesthetics of nationalism and verbal creation - Pantigoso Pecero, Manuel (2019)
The paper begins by pointing out Palma’s actuality through the dialectical link between death and life. It highlights its close link with the National Library, and then conceptualizes tradition as a search for national identity, classic and modern essence, and historical fiction it represents.